Media industries in the digital age : How media businesses work today - Lotz, Amanda D. (Polity Press, 2025)
This book examines how digital technologies have transformed media industries, focusing on changes in production, distribution, and business models. It explores streaming platforms, data-driven strategies, and global market shifts, offering a clear overview of how media companies operate in the digital age.